Pengaruh Penambahan Ekstrak Kulit Terong Ungu pada Tahu yang Mengandung Formalin - Agnes Rantesalu; Winioliski L. O. Rohi Bire; Marni Tangkelangi; Aldiana Astuti (Jurnal Sehat Mandiri, 2024)
Testing for formalin content in food is usually done through laboratory tests using chemicals, making it difficult for people to use it. As an alternative, formalin testing can be done with natural ingredients containing anthocyanins. This study aims to determine the formalin test on purple eggplant skin. This study is an experimental study. The method used is colorimetry by extracting anthocyanins from purple eggplant and testing them on tofu given formalin. Materials such as white tofu, formalin solution, distilled water, ethanol, purple eggplant, and label paper. The tools used in this study were hot plates, dropper pipes, stirring rods, mortars, evaporators, spray bottles, bulbs, and glassware commonly used in chemistry laboratories. This study was conducted in May - December 2023 at the Kupang City Health Laboratory. The results showed an efficient natural method for identifying formalin in food is to use eggplant skin extract. The ideal anthocyanin content in eggplant skin extract can be maintained using the right extraction method. As a result, the use of eggplant skin extract as a test material for formalin can be a practical and environmentally friendly substitute. In conclusion, the use of eggplant skin extract can be a reliable and environmentally friendly solution for detecting formalin in food products. Suggestions are to test the effectiveness of this eggplant skin extract on various types of food. Thus, it can be known how far the reliability of this method in detecting formalin accurately.